More favored - less favored? Women and men in different marital property right systems: A comparative study of marital property rights in the Habsburg Empire during the 18th century - Langer-Ostrawsky, Gertrude; Lanzinger, Margareth (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
Our paper focuses on several central points concerning pre-nuptial negotiations, the results of which were finalized in marriage contracts. There are two opposing systems of the law governing marital property regimes: the regime of matrimonial community of property or joint marital property, Gütergemeinschaft, and the regime of separation of marital property, Gütertrennung We compare two territories of the Habsburg Empire – the County of Tirol with the regime of separation of marital property dominating, and the Archduchy of Austria South of the River Enns (Lower Austria), with matrimonial community of property dominating in rural areas. For each territory, we concentrate on a single landed estate: Fridau-Weißenburg in the case of Lower Austria, and Innichen in the case of Tirol. Innichen was a small market town with a mixed economy based on agriculture and the trades; while the estate of Fridau-Weißenburg was more rural and agricultural and also preindustrial since the middle of the 18th century.